2017
DOI: 10.1080/14756366.2016.1247062
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of novel dual inhibitors of receptor tyrosine kinases EGFR and IGF-1R

Abstract: Novel 4-benzylamino benzo-anellated pyrrolo[2,3-b]pyridines have been synthesized with varied substitution patterns both at the molecular scaffold of the benzo-anellated ring and at the 4-benzylamino residue. With a structural similarity to substituted thieno[2,3-d]pyrimidines as epidermal growth factor receptor (EGFR) inhibitors, we characterized the inhibition of EGFR for our novel compounds. As receptor heterodimerization gained certain interest as mechanism of cancer cells to become resistant against novel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Furthermore, compound 32c significantly inhibited tumor growth in a human NSCLC xenograft mouse model. Hempel et al (2017) identified a series of 4-benzylamino benzo-anellated pyrrolo[2,3-b]pyridines derivatives 33a-33c as novel dual inhibitors of receptor tyrosine kinases EGFR and IGF-1R (Figure 16). According to the anti-proliferative activity assays, the derivative 33a with the most excellent inhibitory activity against EGFR and IGF-1R kinase, with Ki values of 0.072 ± 0.017 and 0.288 ± 0.026 μM, respectively.…”
Section: Miscellaneous Derivativesmentioning
confidence: 99%
“…Furthermore, compound 32c significantly inhibited tumor growth in a human NSCLC xenograft mouse model. Hempel et al (2017) identified a series of 4-benzylamino benzo-anellated pyrrolo[2,3-b]pyridines derivatives 33a-33c as novel dual inhibitors of receptor tyrosine kinases EGFR and IGF-1R (Figure 16). According to the anti-proliferative activity assays, the derivative 33a with the most excellent inhibitory activity against EGFR and IGF-1R kinase, with Ki values of 0.072 ± 0.017 and 0.288 ± 0.026 μM, respectively.…”
Section: Miscellaneous Derivativesmentioning
confidence: 99%
“…2.1 | The role of Klotho in cancer through insulin/IGF signaling pathways Since unusual expression of peptide growth factors and their tyrosine kinases receptor enhances tumor growth and invasion and prevents apoptosis, they are important in the progression of cancer. 19 many growth factors including IGFs contribute to cancer progression and development. 20 The IGF system has a substantial character in regulating various cellular pathways, even in tumor initiation and improvement.…”
Section: Crosstalk Between Klotho and Signaling Pathways In Cancersmentioning
confidence: 99%
“…Since unusual expression of peptide growth factors and their tyrosine kinases receptor enhances tumor growth and invasion and prevents apoptosis, they are important in the progression of cancer . many growth factors including IGFs contribute to cancer progression and development .…”
Section: Crosstalk Between Klotho and Signaling Pathways In Cancersmentioning
confidence: 99%